STUDI KASUS PERUBAHAN LETAK DAN PONDASI TOWER CRANE STATIC MENJADI TOWER CRANE CLIMBING PADA PROYEK AT DISTRICT 8 SENOPATI JAKARTA SELATAN - Hastanto SM; Ratu Gudam Fadhevi (FORUM MEKANIKA, 2016)
The success of a project can be measured on two things, namely the benefits and timelines of the projectcompletion (Soeharto,1997). Both depend on careful planning of the implementation method of use andscheduling tool. The implementation of construction is working using heavy equipment required accurateplanning in order to achieve a project with costs and optimal execution time. Therefore, an analysis of theusage of heavy equipment used is needed, so it can produce proper alternative heavy equipment for theconstruction project. On the development project district 8 Senopati apartments and office tower, SouthJakarta found a problem on one of the tower crane static productivity because it is considered to have a smalland minimal availability section that takes a long time for jacking up, of course, it impedes the progress of theproject, to overcome, the most appropriate step is to move and transform these into climbing tower crane.This research will analyze the most effective position for the tower crane climbing, then the beam must bechecked if it is must be redesigned. After the analysis concluded that the static tower crane converted into aclimbing tower crane void switching positions in buildings area with a beam analysis does not require specialreinforcement.